Theory of Multiple Intelligences in Classrooms: A Case Study of Karachi - Nasim, Foiza; Khan , Fauzia N. (JISR management and social sciences & economics, 2009)
For decades, scientists and scholars have been trying to understand the nature of intelligence and not surprisingly intelligence has always been connected with education. Many theories, models and concepts in education have been accepted and practiced throughout the world. Among them, Howard Gardner’s theory of ‘multiple intelligences’ is considered as a breakthrough as it challenges the traditional view of intelligence. It has been embraced by a range of educational theorists abroad and, significantly, applied by teachers. This study aims at exploring how the theory of multiple intelligences differs from the conventional theories of intelligence, and the extent of effectiveness it brings into the academic design of schools. It also seeks to find what opportunities the schools were providing to children to maximize their learning. It collaborates the findings with the type of intelligences the school caters to and the level at which intelligences are catered to in the private, public and community-based schools.